Manajemen Pendidikan Madrasah Aliyah di Pondok Pesantren ‘Ibadurrahman Nunukan - Nani Fitriono, Eko; Ardatulloh, Fouqi; Anisa; Sephiona; Rafidah, Luluk; Samsinar (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
This study examines the urgency of effective educational management in the context of globalization and rapid social change, focusing on the case of Madrasah Aliyah Pondok Pesantren Ibadurrahman in Nunukan, Indonesia. This study analyzes the effectiveness of Ibadurrahman's educational management through several key aspects: curriculum planning and implementation, teacher quality, educational facilities and resources, evaluation and feedback mechanisms, and community involvement. Despite challenges such as community perception and teacher qualifications, Ibadurrahman demonstrates a commitment to integrating general and religious education, fostering character development, and providing a supportive learning environment. The study concludes by assessing the contribution of Ibadurrahman's educational model to the success of its graduates in higher education and their contribution to society. The findings highlight the importance of a comprehensive approach to educational management that considers both academic excellence and character development in achieving quality education.